The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3889/oamjms.2018.073
|View full text |Cite
|
Sign up to set email alerts
|

The Kapandji Technique of Closed Reduction Using Sommer - Pins in the Treatment of Completely Dislocated Fractures of the Distal Radius in Children

Abstract: BACKGROUND:The fractures of the distal radius are one of the most frequent cases in the pediatric population. The primary way of treating these fractures is conservative, with manual reduction and cast immobilisation. In patients where reduction and retention of the fracture cannot be achieved, a surgical approach is the treatment of choice.AIM:To evaluate the benefits of using the minimally invasive surgical treatment of closed reduction using Sommer - pins in the treatment of the fractures of the distal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The functional outcome was comparable with the study done by Kamiloski et al 21 At final follow up in this study, patients did not complain of pain except two cases, 26 patients were satisfied but two patients were moderately satisfied as per modified Mayo wrist score. Among two patients one had associated open fracture at ulna and supracondylar fracture, and another had communited fracture of radius.…”
Section: Discussionsupporting
confidence: 89%
“…The functional outcome was comparable with the study done by Kamiloski et al 21 At final follow up in this study, patients did not complain of pain except two cases, 26 patients were satisfied but two patients were moderately satisfied as per modified Mayo wrist score. Among two patients one had associated open fracture at ulna and supracondylar fracture, and another had communited fracture of radius.…”
Section: Discussionsupporting
confidence: 89%
“…These are the excessive displacement of the fracture during the presentation and insufficient correction after the reduction maneuver. Several authors have identified risk factors for distal radius fractures, which can be categorized into two categories: primary and secondary causes [15]. The primary causes include being over 9 years of age, a complete displacement at the baseline, fractures of greater than 50% displacement, greater than 20° angles, oblique fracture lines, comminuted fractures, dorsal bayonet fractures, and ipsilateral distal ulna fractures [15].…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of using the minimally invasive surgical treatment of closed reduction using Sommer -pins with Kapandji technique in 48 completely dislocated fractures of the distal radius after ineffective non-surgical treatment of children aged six to 14 years during the period between 2012 and 2017 are evaluated (Kamiloski et al, 2018). The anatomic reduction is easily achieved with this technique in every case.…”
Section: Discussionmentioning
confidence: 99%